Pre hospital pediatric trauma: EMS experience, improving the prehospital care and road map for the future - G V Ramana Rao; Geethanjali Ramachandra; Srinivas Puppala; Aruna Gimkala; Rani Janumpally (Wolters Kluwer Medknow Publications, 2017)
Objectives: To study the Pediatric (age 0-14 years) prehospital trauma pattern for year 2015 in Telangana (TS) and Andhra Pradesh (AP). To highlight the experiences of pre hospital training and injury prevention measures in selected geographies and to recommend road map for the future. Methods and Materials: Data collected from Primary sourced computer aided dispatch (CAD) 108 emergency medical response services (EMS) at Gunupati Venkata Krishna Reddy (GVK) Emergency Management and Research Institute (EMRI). Results: Total 9517 children were identified. 5563(58%) stabilised and transported to the hospital. 23% died at the time of EMS arrival. First aid given in 3% and 16% found to be stable and not transported. Medical guidance sought in 30%. Majority were school children 5 to 14years (82%), boys (68%). Evenings 3-7pm, Sundays, month of May saw highest peak. 51% belonged to rural area. Ranga Reddy district had the highest incidence. Government hospitals received 69%. Vehicular trauma calls were higher (75%) than Non-Vehicular (25%). Two wheeler (motorcycle and cyclist) injuries (79%) among vehicular; skid and fall from height in non-vehicular (81%) were top most causes.Conclusion: Two wheeler accidents, skid and fall from height are the most common causes. Such research studies should be an annual feature in all EMS systems. Detailed countrywide study is needed on the use of helmet, speeding, mobile usage, mechanism of fall and place to identify the role of preventive measures. There is an urgent need to improve pre hospital trauma care and implement preventive strategies to stem the tide of trauma deaths.